Recall and recognition of in-game advertising: the role of game control - Herrewijn, Laura; Poels, Karolien (Frontiers in Psychology, 2014)
Digital gaming has become one of the largest entertainment sectors worldwide, increasingly turning the medium into a promising vehicle for advertisers. As a result, the inclusion of advertising messages in digital games or in-game advertising (IGA) is expected to grow steadily over the course of the following years. However, much work is still needed to maximize the effectiveness of IGA. The aim of the study was to contribute to IGA effectiveness research by analyzing the impact of two factors on the processing of IGA in terms of brand awareness. The primary objective was to investigate the effect of a person’s sense of involvement related to the control and movement mechanisms in a game (i.e. kinesthetic involvement). A within-subjects experiment was conducted in which control over a racing game was varied by manipulating game controller type, resulting in two experimental conditions (symbolic versus mimetic controller). Results show that the variation in game controller has a significant effect on the recall and recognition of the brands integrated into the game, and that this effect can be partially brought back to players’ perceived control over the game: when a game is easier to control, the control mechanisms require less conscious attention, freeing attentional resources that can be subsequently spent on other elements of the game such as IGA. A second factor that was taken into account in the study was brand prominence. The influence of both the size and spatial position of in-game advertisements was examined. Findings demonstrate that there are significant changes in effectiveness between different types of placements. Spatial position seems to be the most important placement characteristic, with central brand placements obtaining the highest recall and recognition scores. The effect of ad size is much smaller, with the effectiveness of the large placements not differing significantly from the effectiveness of their smaller counterparts.